Facilities and difficulties experienced by the family in caring for children with special health needs (Research, Society and Development, 2020)
Objectives: to know the family's facilities and difficulties in caring for children with special health needs. Methodology: of exploratory and descriptive qualitative research carried out with sixteen family members of children with special health needs from a Neonatal Intensive Care Unit in southern Brazil. Data collection took place between March and July 2016 through interviews and submitted to thematic analysis. Approved by the Health Research Ethics Committee (CEPAS) under number 063/2014. Results: as facilities mentioned the encouragement and preparation acquired during hospitalization in the Neonatal Intensive Care Unit, having access to the different health services necessary for the treatment of the child and receiving a financial benefit from the government, having a family support network, recognition of the child's abilities and the fact that the child feels with high self-esteem. As difficulties they referred to the negative impact that hospitalization can represent, fear of the child's loss, having to divide themselves between the child in the hospital and the rest of the family, also affecting the marriage, lack of time for the caregiver's self-care, and to impose limits on children's education. Conclusion of the study: family care is complex, and it is necessary to review and reflect the care practices by health professionals, improving interactive methods with the family to support them in experiencing care for children with special health needs.